Management of small intestinal bacterial overgrowth by pediatric gastroenterologists in Spain. - Martin‐Masot, Rafael; Molina Arias, Manuel; Díaz Martín, Juan José; Cilleruelo Pascual, María Luz; Gutiérrez Junquera, Carolina; Donat, Ester; Román Riechmann, Enriqueta; Navas-López, Víctor Manuel (Arán Ediciones, 2020)
Background: small intestinal bacterial overgrowth (SIBO) is a heterogeneous condition with nonspecific symptoms. This study aimed to report its management by pediatric gastroenterologists in Spain. Methods: a descriptive study was performed by means of a survey sent to 184 active members of the Spanish Society of Pediatric Gastroenterology, Hepatology and Nutrition (SEGHNP). Results: one hundred and forty-eight responses (80.4 %) were received. Forty-four patients had no predisposing condition, 31.1 % used antibiotics followed by probiotics, 33.1 % antibiotherapy concomitant with probiotics, 24.3 % only antibiotics and 10.8 % only probiotics. The diagnosis was established via clinical parameters in 73.8 % of participants and the therapeutic response was checked only by clinical data in 90 %. Conclusions: there is high variability in the management of SIBO among pediatric population in Spain.
Keywords: Intestino delgado - Enfermedades bacterianas; Pediatría - Investigación; SIBO; Pediatrics